An inclusive numerical framework to assess the role of feedstock features on the quality of cold spray deposits. (December 2022) - Ardeshiri Lordejani, A.; Colzani, D.; Guagliano, M.; Bagherifard, S.
Graphical abstract: Highlights: An inclusive numerical framework is developed to assess the role of feedstock features (size, morphology, oxidation extent and impact angle) on cold spray deposit quality. The efficiency of multiple FEM approaches including Lagrangian, smoothed particle hydrodynamics (SPH), and coupled Eulerian-Lagrangian is evaluated. Deposit quality indicators involving critical velocity, particle flattening, and porosity have been assessed as a function of each powder feature. Comparison with experimental data confirmed the capacity of the proposed framework to tune the deposit properties as a function of a wide range of primary and secondary powder characteristics. Abstract: Cold spray technology provides unique capabilities for coating, repair, and additive manufacturing. However experimental trial and error to optimize deposit quality indexes, that rely on powder characteristics, can be costly and tedious. In this research, multiple finite element modelling approaches were compared regarding their capability and shortcomings to analyze the role of major powder features on deposit properties. Lagrangian and CEL methods were selected as the most robust approaches for analyzing the single/multi-particle impact condition, respectively. An intricate algorithm was introduced to accurately evaluate the effect of parameters including particle size, shape, oxidation extent, and impact angle on the deposition indicators such as critical velocity, particle flattening, and deposit porosity. The results exhibited a good agreement with the reported experimental data, confirming the capacity of the proposed numerical framework to tune the deposit properties as a function of a wide range of feedstock characteristics. It was concluded that for successful deposition, the effect of various powder properties and their respective effect and contribution towards plastic deformation should be taken into account. The results indicated that for a given particle velocity, smaller particle, more irregular morphology, thicker oxide layer, and smaller impact angle will result in limited particle deformation and a lower possibility of successful adhesion.